The The Effectiveness of WhatsApp Social Media Utilization in Farmer Group Communication: A Study in Wonosari Village, Tanjung Morawa District, North Sumatra - Syafi'i, Arif; Anang Anas Azhar (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
AbstrakPenelitian ini bertujuan untuk menganalisis efektivitas penggunaan media sosial WhatsApp dalam komunikasi kelompok tani di Desa Wonosari, Kecamatan Tanjung Morawa, Sumatera Utara. Dalam era digital, penggunaan media baru telah mengubah cara berkomunikasi, termasuk dalam sektor pertanian. Kelompok tani sebagai komunitas berbasis agraris mulai memanfaatkan WhatsApp untuk koordinasi, berbagi informasi pertanian, serta mempermudah komunikasi dengan Penyuluh Pertanian Lapangan (PPL). Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode wawancara mendalam, observasi, dan kajian pustaka. Hasil penelitian menunjukkan bahwa WhatsApp memberikan efektivitas yang signifikan dalam komunikasi kelompok tani, terutama dalam penyebaran informasi yang lebih cepat, koordinasi yang lebih efisien, serta peningkatan keterlibatan anggota. Namun, terdapat kendala dalam adopsi teknologi, khususnya bagi anggota kelompok tani yang lebih tua dan kurang terbiasa dengan media digital. Selain itu, tantangan lain adalah adanya penyebaran konten yang kurang relevan dalam grup WhatsApp. Untuk mengatasi hambatan tersebut, diperlukan pelatihan penggunaan media sosial bagi anggota yang belum terbiasa serta pengelolaan grup yang lebih sistematis, Dengan adanya dukungan dari pemerintah dan PPL. Studi ini memberikan wawasan mengenai perubahan perilaku komunikasi di sektor pertanian akibat adopsi teknologi baru dan implikasinya dalam pengembangan kelompok tani di era digital. Kata kunci: WhatsApp, komunikasi kelompok tani, difusi inovasi, media sosial, pertanian digital Abstract This study aims to analyze the effectiveness of the use of WhatsApp social media in farmer group communication in Wonosari Village, Tanjung Morawa District, North Sumatra. In the digital era, the use of new media has changed the way we communicate, including in the agricultural sector. Farmer groups as agrarian-based communities have begun to use WhatsApp to coordinate, share agricultural information, and facilitate communication with Field Agricultural Extension Workers (PPL). This study uses a descriptive qualitative approach with in-depth interviews, observations, and literature review methods. The results show that WhatsApp provides significant effectiveness in farmer group communication, especially in faster information dissemination, more efficient coordination, and increased member engagement. However, there are obstacles in the adoption of technology, especially for members of farmer groups who are older and less familiar with digital media. In addition, another challenge is the spread of less relevant content in WhatsApp groups. To overcome these obstacles, training in the use of social media for members who are not used to it is needed as well as more systematic group management, with support from the government and PPL. This study provides insight into the changes in communication behavior in the agricultural sector due to the adoption of new technologies and their implications in the development of farmer groups in the digital era. Keywords: WhatsApp, farmer group communication, innovation diffusion, social media, digital agriculture